Energy consumption component analysis mathematical model of grinder energy unit. (2018) - Zhou, Yan; Zhang, Hua; Yan, Wei; Ma, Feng; Li, Gongfa; Chang, Wenjun
Aiming at the characteristics of grinding machine with many energy sources, this paper studied the energy consumption of grinding machine from the aspect of energy consumption, analysed the energy consumption of each energy consumption unit of grinding machine, based on the energy balance equations of each energy consumption unit of grinder, the mathematical model of energy consumption component analysis of energy consumption unit is established. The model can provide a new theoretical method for energy efficiency analysis and prediction in the process of grinding machine. At the same time, it builds multi-source information fusion between machine tool and workpiece to support the production process decision-making, which is good for the manufacturing industry to become intelligent and green and the direction of development.